2021
DOI: 10.21037/atm-21-3020
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between hepatitis B virus infection and the efficacy of camrelizumab in combination with apatinib therapy in patients with hepatocellular carcinoma: a multicenter retrospective cohort study

Abstract: Background: The interaction between hepatitis B virus (HBV) load and anti-programmed cell death (PD)-1 in combination with (+) antiangiogenic therapy remains controversial, especially for hepatocellular carcinoma (HCC) patients. This study sought to explore the effects of HBV load and antiviral therapy on anti-PD-1+ antiangiogenic therapy, and the rate of HBV reactivation during anti-PD-1+ antiangiogenic treatment.Methods: We performed a multicenter retrospective cohort study of camrelizumab combined with apat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…HBV DNA is often associated with poor prognosis in the local or systemic treatment of liver cancer ( 21 28 ). However, during PD-1/PD-L1 ICI treatment, patients with HBV-related liver cancer had a similar tumor response to that of all patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HBV DNA is often associated with poor prognosis in the local or systemic treatment of liver cancer ( 21 28 ). However, during PD-1/PD-L1 ICI treatment, patients with HBV-related liver cancer had a similar tumor response to that of all patients.…”
Section: Discussionmentioning
confidence: 99%
“…In most clinical trials for PD-1/PD-L1 ICIs, liver cancer patients with HBV infection were required to have a baseline HBV load <100 IU/mL for eligibility; therefore, the effect of baseline viral load on clinical outcomes could not be assessed. However, several studies have enrolled patients with a high viral load, suggesting an absence of correlation between baseline HBV viral load and patient OS and PFS during PD-1/PD-L1 treatment; however, the presence or absence of antiviral therapy during immunotherapy could affect tumor prognosis ( 27 , 28 ).…”
Section: Introductionmentioning
confidence: 99%
“…Target-immunity combination therapy as a neoadjuvant option for resectable HCC can reduce the 1-year postoperative recurrence rate and improve the 1-year survival rate without compromising the safety of surgery ( 45 ). In addition, several studies have shown that HBV load does not affect tumor response in HCC patients treated with camrelizumab in combination with apatinib ( 46 ). The combination of camrelizumab and apatinib for advanced HCC with portal vein tumor thrombosis has good efficacy and controllable side effects, and is worth promoting in the clinic ( 47 ).…”
Section: Clinical Applicationsmentioning
confidence: 99%
“…Sun et al (2020) found no significant correlation between clinical outcomes and HBV loads in HCC patients receiving the PD-1 inhibitor. In addition, Yuan et al (2021) found that HBV loads did not affect the short-term efficacy of the PD-1 inhibitor combined with antiangiogenic therapy for HCC patients. NAFLD refers to a clinical syndrome characterized by excessive deposition of fat in liver cells, apart from alcohol and other definite liver damage factors (Eslam et al, 2020).…”
Section: Discussionmentioning
confidence: 96%